A Avenida Nóide Cerqueira no traçado urbano da cidade de Feira de Santana, Bahia - Andrade, Mariana Sousa de (2018)
The research analyzes the urban design of Feira de Santana – Bahia, based on the transformations, especially concerning the road network. Considering the urban design as language, which, in case, is the focus of this analysis, and the understanding of city social practices, the main avenues of the city have been studied. Their modifications have been related to strategies of modernization and planning for a better understanding of the design of Nóide Cerqueira Avenue, object of this study. Parting from bibliographic analysis, design and urban landscape have been analyzed through pictures, maps and technical visits in order to understand the characteristics of the city road network. It was noticed that all avenues influence in the change of the design of the areas they are constructed, being considered formation vectors, expansion and urban changes. The group of this road network, formed by wide avenues, interfere directly in the flow of vehicles in the city and, consequently, in the range of urban neighborhood. One can understand that the construction of Nóide Cerqueira Avenue follows some purposes common to most avenues constructed before it, but it also shows some particular characteristics. However, if there is no specific planning, its outline might present the same problems of other avenues.